Defining Outpatient Hip and Knee Arthroplasties: A Systematic Review. Issue 8 (15th April 2021) - McClatchy, Samuel G.; Rider, Carson M.; Mihalko, William M.; Pharr, Zachary K.; Toy, Patrick C.
Abstract : Introduction: The term "outpatient" has a variety of meanings regarding the location of arthroplasty and the duration of stay postoperatively. The purpose of this systematic review was to evaluate the literature and more accurately define the term "outpatient." Methods: A PubMed search (2014 to 2019) using the terms "outpatient AND arthroplasty" identified 76 studies; 35 studies that met the inclusion criteria were assessed to determine the definition of "outpatient." The level of evidence, type of arthroplasty, location of surgery (hospital or ambulatory surgery center [ASC]), approach used for hip arthroplasty, number of patients, number of surgeons, and length of time the patients were kept at the location after surgery were evaluated. Results: Arthroplasties analyzed were total hip (11), total knee (seven), unicompartmental knee (five), and hip and knee (12). Only 16.8% of surgeries defined as outpatient hip or knee arthroplasty were done in a freestanding ASC, and 44.2% of patients defined as outpatients were kept overnight for the 23-hour observation. Discussion: We propose "DASH" (Discharge from ASC to Home) as a new term to define arthroplasties done in an outpatient setting with the patient discharged home the same day.